Mathematics
Using remainder theorem factorise 4x3 + 7x2 - 36x - 63 completely.
Factorisation
3 Likes
Answer
Substituting x = 3 in 4x3 + 7x2 - 36x - 63, we get :
⇒ 4x3 + 7x2 - 36x - 63
⇒ 4(3)3 + 7(3)2 - 36(3) - 63
⇒ 4 × 27 + 7 × 9 - 108 - 63
⇒ 108 + 63 - 108 - 63
⇒ 0.
So, x - 3 is the factor of 4x3 + 7x2 - 36x - 63.
On dividing 4x3 + 7x2 - 36x - 63 by (x - 3) we get,
∴ 4x3 + 7x2 - 36x - 63 = (x - 3)(4x2 + 19x + 21)
= (x - 3)(4x2 + 12x + 7x + 21)
= (x - 3)[4x(x + 3) + 7(x + 3)]
= (x - 3)(4x + 7)(x + 3).
Hence, 4x3 + 7x2 - 36x - 63 = (x - 3)(4x + 7)(x + 3).
Answered By
1 Like
Related Questions
If matrix M = , find M2 - 4M - 4I.
The given figure shows two congruent circles touching each other externally and with centers O' and O as shown. PC is tangent to the circle with center O. Find :
(i)
(ii)
Vertex A of triangle ABC is (-3, 5) and mid-points of the sides AB and AC are (-4, 4) and (2, -2) respectively. Find :
(i) co-ordinates of vertices B and C.
(ii) equation of line through vertex C and parallel to side AB.
Prove that :
sin A(1 + tan A) + cos A(1 + cot A) = sec A + cosec A